2022
DOI: 10.2478/amns.2022.2.0174
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Application of Quantile Regression Equation in Forecasting Financial Value at Risk in Financial Markets

Abstract: With the development of the times and the progress of science and technology, the financial market is constantly reformed and China's financial industry is gradually modernized. However, China's economy has been in the stage of rough growth for a long time, which has led to low efficiency in the allocation of financial resources and unreasonable use of funds, and this has seriously restricted the whole social production activities and the stability and sustainable and healthy development of the national econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…He found that this model outperformed both the GARCH-based methods and the CAViaR models. Chen and Chen (2002) found that calculating VaR at the Nikkei 225 index using quantile regression outperformed the conventional variance-covariance approach. In addition, Shim et al (2012) employed semiparametric support vector quantile regression (SSVQR) models to estimate VaR on return data on the S&P 500, NIKEI 225, and KOSPI 200 indices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…He found that this model outperformed both the GARCH-based methods and the CAViaR models. Chen and Chen (2002) found that calculating VaR at the Nikkei 225 index using quantile regression outperformed the conventional variance-covariance approach. In addition, Shim et al (2012) employed semiparametric support vector quantile regression (SSVQR) models to estimate VaR on return data on the S&P 500, NIKEI 225, and KOSPI 200 indices.…”
Section: Literature Reviewmentioning
confidence: 99%